2015
DOI: 10.1038/srep16389
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion Diffusion-weighted Magnetic Resonance Imaging for Monitoring the Early Response to ZD6474 from Nasopharyngeal Carcinoma in Nude Mouse

Abstract: Early therapeutic effects of anti-angiogenic agent ZD6474 upon nasopharyngeal carcinoma (NPC) in nude mouse were monitored by using intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI). Mice bearing NPC underwent IVIM DWI at baseline and after 1, 3, and 7 days of treatment with ZD6474 or vehicle (n = 12 per group). Parameters of apparent diffusion coefficient (ADC), true diffusion coefficient (D), perfusion fraction (f), and blood pseudodiffusion coefficient (D*) at different time points were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Because the IVIM parameter f should represent the "incoherently flowing" blood volume, it is expected to correlate with histological microvascular density (MVD). Accordingly, most published work found a fair to good 44 correlation between perfusion fraction f and MVD (Figure 4), for example in a rat brain glioma model (r = 0.56, p < 0.05), 45 in a mouse model of colorectal cancer (r = 0.75, p < 0.001), 46 in human pancreatic ductal adenocarcinomas and neuroendocrine tumors (r = 0.85, p < 0.01), 47 in a rabbit liver tumor model (r = 0.47, p = 0.02), 48 and in a mouse model for nasopharyngeal carcinoma after anti-angiogenic treatment (r = 0.52, p = 0.02). 49 On the other hand, Eberhardt et al 50 found no correlation between average f and average MVD in five abdominal organs in mice (r = −0.50, p = 0.391), but found a significant correlation between D* and MVD (r = 0.90, p = 0.037).…”
Section: Correlation With Histologymentioning
confidence: 98%
See 1 more Smart Citation
“…Because the IVIM parameter f should represent the "incoherently flowing" blood volume, it is expected to correlate with histological microvascular density (MVD). Accordingly, most published work found a fair to good 44 correlation between perfusion fraction f and MVD (Figure 4), for example in a rat brain glioma model (r = 0.56, p < 0.05), 45 in a mouse model of colorectal cancer (r = 0.75, p < 0.001), 46 in human pancreatic ductal adenocarcinomas and neuroendocrine tumors (r = 0.85, p < 0.01), 47 in a rabbit liver tumor model (r = 0.47, p = 0.02), 48 and in a mouse model for nasopharyngeal carcinoma after anti-angiogenic treatment (r = 0.52, p = 0.02). 49 On the other hand, Eberhardt et al 50 found no correlation between average f and average MVD in five abdominal organs in mice (r = −0.50, p = 0.391), but found a significant correlation between D* and MVD (r = 0.90, p = 0.037).…”
Section: Correlation With Histologymentioning
confidence: 98%
“…Several studies have found IVIM of interest in monitoring tumors after antiangiogenic drug therapies, and might be helpful to separate responders from non‐responders. In a nasopharyngeal carcinoma mouse model, Cui et al found a significant decrease in f and D * in a group treated with antiangiogenic therapy compared with a control group, as soon as 1 day after treatment. In a hepatocellular carcinoma xenograft mouse model, Yang et al found a significant decrease in f at 7 days after antiangiogenic treatment, and a significant increase at 21 days.…”
Section: Application In Perfusion‐related Clinical Situationsmentioning
confidence: 99%
“…Using this wellestablished and validated animal model, we showed that IVIM is capable of assessing the changes in both tumor perfusion and diffusion in response to antivascular treatments, without the need for contrast media injection. The biexponential IVIM model can be used to estimate perfusion-related parameters, including the blood pseudo-diffusion coefficient (D Ã ), indicative of blood flow, and the perfusion fraction (f), indicative of the fractional volume of active capillaries in the tumor, by fitting to fit DWI data acquired at multiple b values (22), which provides a simple and practical way to quantitatively assess the perfusion in small vessels and capillaries, namely microperfusion (23)(24)(25)(26)(27)(28)(29)(30)(31). In contrast, DCE-MRI measures classic perfusion, which is the pharmacokinetics of the injected tracer, and the volume transfer constant, K trans , represents tissue perfusion and permeability (39).…”
Section: Discussionmentioning
confidence: 99%
“…The IVIM method was originally developed by Le Bihan in 1986 using a biexponential model to separate the diffusionweighted signal into a pure diffusion fraction and a perfusion dominated "pseudo-diffusion" fraction (22), permitting the simultaneous assessment of tissue diffusion and microperfusion (22)(23)(24). Recently, in both preclinical and clinical studies, there has been renewed interest in utilizing the perfusion-related parameters of IVIM DWI, including the blood pseudo-diffusion coefficient (D Ã ) and the perfusion fraction (f), to quantify microvessel perfusion in solid tumors (25)(26)(27)(28)(29)(30)(31). The IVIM method is considered an attractive approach because it can assess microperfusion in the tumor without the need for exogenous contrast agents, making it possible to be used within a short time interval for the evaluation of therapeutic response, even in patients with renal insufficiency, or in patients with contraindications to contrast agents (24,32).…”
Section: Introductionmentioning
confidence: 99%
“…IVIM parameters have been used in the monitoring of tumors in patients treated with drugs, as antiangiogenic and vascular target agents applied outside the brain ( Cui et al, 2015 ; Joo et al, 2016 ; Joo et al, 2014 ; Marzi et al, 2015 ; Yang et al, 2017 ).…”
Section: Neurological and Neurovascular Applicationsmentioning
confidence: 99%